Efficacy, tolerability, and safety of a combination including metronidazole, miconazole, Gotu kola, polymixin, and neomycin in soft vaginal capsules for the treatment of bacterial vaginosis - del Castillo S., Angélica (2013)
Introduction: Bacterial vaginosis (BV) is a polymicrobial syndrome, in which the normal dominant flora consisting in Lactobacillus is replaced by polymicrobial flora. The prevalence of BV in Peru varies between 27 and 43.7%. The Centers for Disease Control and Prevention suggest therapy for BV in symptomatic women should include oral/gel metronidazole or clindamycin cream. We proposed in this study to evaluate the efficacy, tolerability and safety of the combination of metronidazole, miconazole, Gotu kola (Centella asiatica), polymixin, and neomycin in soft capsules, for the treatment of BV. Material and Methods: This investigation was an open, observational, and prospective study, which allowed us to evaluate the efficacy, tolerability and safety of the aforementioned combined therapy administered in soft capsules. Results: The study included 61 patients with a mean age of 29.28 years (range, 18-48) and 93.4% had a history of abnormal vaginal discharge. Two visits took place during the study, the first for making the diagnosis and initiating therapy, and the second was the post-treatment control. Three patients did not have a second visit and 8 did not record all the information required to define the therapeutic response. The second visit took place after 21 days on average. The main signs and symptoms at the first visit were vaginal discharge at diagnosis (100.0%), vaginal discomfort (85.2%), dyspareunia (70.5%) and lower abdominal pain (57.4%), which were significantly reduced (p <0.05) in the second visit after treatment. The amine test was positive in 93.4% of cases in the first visit and in 15.5% of cases in the second visit (p <0.05). From the initial population in the study, only 53 women are evaluable for efficacy. An overall response rate in 44 women (83.02%) was achieved with the soft capsule combination treatment. Adverse events were reported in only one case. Nearly three quarters (78.7%) of women who used the soft capsule combination found it easy or very easy to use. Regarding comfort, 65.6% of women reported feeling comfortable or very comfortable. More than half (57.4%) of women who had previous experience using ovules declared that the soft capsule combination was better or much better compared to previous therapies. Conclusions: In this study, the soft capsule combination proved to be efficient and effective, with good tolerance and safety for patients, resulting in adherence to treatment and ensuring compliance.